MENENTUKAN LUAS DAERAH DI BAWAH KURVA EKSPONEN MENGGUNAKAN MICROSOFT MATHEMATICS 4.0 - Hery Kristanto, Vigih (Widya Warta, 2013)
In the year 2010, Microsoft as one of the biggest software companies introduced an application in the form of free software, that is,MicrosoftMathematics 4.0. This application is used to solve some problems of school mathematics, such as: statistics, calculus, equation and equation system, the painting of two dimension graph, three dimension graph and triangle. Related to this phenomenon, the writer tried to applyMicrosoftMathematics 4.0 to determine the width of area below/under exponent curve limited by axis X, line x = a and line x = b with the steps: (1)Graphing Equations and Functions-2D-Cartesian-Add-Input-Graph and (2) Worksheet-Input-Enter-Output.